Managing cultural differences - Moran, Robert T. 1938-; Abramson, Neil R. 1953-; Moran, Sarah V. (Sarah Virgilia) 1972- (Routledge, 2014)
The world of business for all organizations in the twenty-first century is global, interdependent, complex, and rapidly changing. That means sophisticated global leadership skills are required more than ever today. Individual and organizational success is no longer dependent solely on business acumen. Our ability to understand, communicate, and manage across borders, countries, and cultures has never been as important as it is now. The understanding and utilization of cultural differences as a business resource is a key building block as companies rely on their global reach to achieve the best profit and performance. For this reason, international business and cross-cultural management are key topics in undergraduate business, MBA, and executive education programs worldwide as companies and institutions prepare current and future business leaders for the global marketplace. This exciting new edition of the highly successful textbook, Managing Cultural Differences, seeks to guide students and any person with global responsibilities to understand how culture fits in a changing business world, how to gain a competitive advantage from effective cross-cultural management, and gives practical advice for doing business across the globe. With updated content, new case studies, and a new author team, Managing Cultural Differences is required course reading for undergraduates, postgraduates, and MBA students alike, as well as being of significant value for anyone who sells, purchases, travels, or works internationally.